Pembiasaan Zikir Asmaul Husna dan Shalat Berjamaah - Machfud Syaefudin; Wirayudha Pramana Bhakti (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
Research on the presence or absence of the influence of the intensity of reading Asmaul Husna dhikr and Dhuhur Congregation Student prayer on the level of self-control of MA students in the City of Pekalongan. The first research hypothesis, namely there is a positive and significant effect between the intensity of reading the Asmaul Husna dhikr on student self control. Secondly, there is a positive and significant influence between the habit of performing Dhuhr prayer in congregation on students' self control. The research method in the form of quantitative research methods. There is a significance value of t for the Asmaul Husna reading habit variable is 0.056 and the value is smaller than the α probability set at 0.495 (0.495> 0.05). Tests show H0 is accepted and Ha is rejected. The significance value of t for the variable performing the midday prayer is 0.119 and the value is greater than the α probability set at 0.05 (0.095> 0.05). Tests show H0 is accepted and Ha is rejected. Based on the partial linear regression test results partially, it can be concluded that the intensity of the habit of reading Asmaul Husna and Dhuhr Prayer in congregation has a positive and significant effect on student self-control